Borders of the Self in Alfredo Véa's The Silver Cloud Café - Roberto Cantú (Studies in 20th & 21st Century Literature, 2001)
I am proposing an analysis of a novel by Alfredo Véra, Jr., The Silver Cloud Café (1996). As the author of a narrative trilogy that includes La Maravilla (1993), and Gods Go Begging (1999), Véa has produced, in The Silver Cloud Café, a novel that is central to the trilogy's interpretation. In my analysis, I discuss how Véa's novels question borders of the self—understood as ethnic or racial—through notions of a personal education (in La Maravilla, Alberto's; in The Silver Cloud Café, Zeferino's) in which characters count on the pedagogical guidance of Yaqui shamans, manongs from the Philippine Islands, Mexican braceros, and, in Alberto's case, a Spanish grandmother. In terms of the challenges that Véa's novels make on the reader, I argue that such difficulties derive from fundamental notions that Véa embraces regarding the writer, the literary text, and the reader. Moreover, Véa questions minimalist tendencies in the United States that reduce persons to one racial or ethnic identity. As a historical novel, Silver Cloud turns into an archaeological site where the imperial histories of Spain and the United States are read as the narrative's intertextual memory. My analysis will be centered on the novel's rhetoric of memory and forgetfulness, and on its visionary impulse that—taken mostly from the Gnostics, American Transcendentalists, and modern Latin American novelists—one could read as a critique of America as well as the reclaiming of literary traditions that redefine the conventional limits of Chicano literature. These traditions extend to prophetic biblical texts, Augustine, Dante, and—among other literary figures—to modern Latin American writers, thus illuminating Véa's continued reflection on a world in decay and on the corresponding visions or revelations of its regeneration. Although present in Chicano literature in novels by Rudolfo, Anaya, Montserrat Fontes, Arturo Islas, and José Antonio Villarreal, this apocalyptic tradition has for the most part been ignored by Chicano/a writers. This last point has obvious implications for any study of the Chicano historical novel and of the cultural borders that often separate it from other literary traditions.
Keywords: novel; Alfredo Véa Jr.; The Silver Cloud Café; La Maravilla; Gods Go Begging